EFEKTIFITAS TOOLBOX MEETING PADA KESELAMATAN DAN KESEHATAN KERJA JURU IKAT DI PT PELABUHAN PENAJAM BANUA TAKA - Sunyanti, Sunyanti; Fuadi , Yan; Swandito , Adji; Rohanto, Edy (IDENTIFIKASI, 2023)
The implementation of SMK3 in PP 50 in 2012, mentioned that K3 communication is part of supporting activities for the prevention of work accidents. One of the prevention efforts in K3 is to implement safety communications programs, including the implementation of safety talk or toolbox meetings at work. Toolbox meetings are defined as informal job training, these talks are designed to convey a safety message to improve safety and prevent work-related incidents (Varley &Boldt, 2002). The implementation of the Toolbox Meeting is part of supporting activities for the prevention of work accidents. This research aims to find out the effectiveness of K3 communication in the Toolbox Meeting at PT Pelabuhan Penajam Banua Taka. This research is Quantitative with the SPSS software banyuan and the Depdagri Effectiveness Test Theory (2009). The population in this study was a Worker of the Oprasional Department of Juru Ikat PT Pelabuhan Penajam Banua Taka which amounted to 76 people, with a sample of 43 people. The sampling technique used is probability sampling, namely by simple random sampling. Using Kuisoner Likert with 35 positive statements in each sub-variable sourced from the theory of Ron Ludlow &Fergus Panton, the K3 Communication Barrier. The result of calculating the effectiveness of the implementation of the meeting toolbox is 66.67% which is Quite Effective. Strengthened by observations and interviews that found a less wide-ranging perspective or called Perceptual Distraction that causes K3 Communication in toolbox meetings to be hampered. Then on the Culture Difference factor that cultural differences in this case K3 culture and discipline culture that has not worked well so as to inhibit effective communication. In the Poor Choise Communicaton Channel factor in this case the selection of toolbox meeting material, they feel saturated with Toolbox Meeting Material that is less attractive so that it relates to the No Feed Back factor, namely workers are less enthusiastic in responding during the implementation of toolbox meetings.